Ruhaniyatu al-Khat al-Qur’ani li al-Khatati Saiful ‘Adnan - Musthofa, Tulus; Huda, Nurul; Gunawan, Fahmi; Hasan, Abd Rauf bin (Universitas Islam Negeri Raden Intan Lampung, 2020)
The art of calligraphy painting by Syaiful Adnan and its beauty are interesting to study due to their distinctive characteristics. Adnan’s script or type of writing differs from the standard style of script from the Middle East. In his hand, creative processes and various dynamics of aesthetic aspects tend to glide calmly. Syaiful Adnan has had solo and collective exhibitions at home and abroad which present the holy verses of the Qur'an as well as hadith and Mahfudzot or words of wisdom as central themes. This research uses archival research method to study various references and documentation as well as direct interviews. Data is analysed inductively by organizing it, describing it into units, synthesizing, composing into patterns, choosing what is important and what will be studied, and present it in this article. The study discovered that spiritual aspects found in Syaiful Adnan’s calligraphy painting is a form of representation of monotheism and dhikr. The oneness of Allah can easily be understood through a series of verses of the Qur'an that contain all the greatness, majesty and omnipotence of the Almighty. From here we can see that the works of Syaiful Adnan were made a communication medium for the audience's awareness and Syaiful Adnan's own self. Furthermore, Syaiful's calligraphy is also a form of visual dhikr, reading and realizing continuously about the verses of God.